Overcoming the strength-ductility trade-off of an AZ31 matrix composite reinforced by in-situ spherical Al3Fe nanoparticles. (1st August 2022) - Xu, Z.Y.; Fang, C.F.; Wang, N.; Wang, R.; Zhang, X.P.; Wang, Y.M.
Abstract: Hard second-phase particles in Mg matrix composites deliver effective strengthening effect but in most cases accompanied by the loss of ductility. In this study, a series of Al3 Fe nanoparticles in-situ reinforced Mg matrix composites are made by using AZ31 alloy and precursor Fe nanopowder. Among these AZ31 alloy and composites, the as-rolled 0.5 wt% Al3 Fe/AZ31 composite shows the highest yield and ultimate tensile strength, while being slightly more ductile than the AZ31 alloy. The activation of non-basal dislocation slip has been revealed in the tensile strained microstructures, which results in a higher early stage strain hardening rate and late stage uniform elongation. This sort of Mg matrix composite offers some insight on overcoming the strength ductility trade-off of Mg matrix composites.